2020
DOI: 10.3390/su12166646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smartphone Use on Emotional, Cognitive and Educational Dimensions in University Students

Abstract: The use of mobile devices is one of the increasingly interactive methodologies widely promoted within the European Higher Education Area. It is, therefore, necessary to determine the potential effects of their excessive use on psychological and educational variables. The aim of the present study was to assess smartphone addiction and its relationship with emotional, cognitive, and educational dimensions in university students. Participants comprised 144 university students aged between 19 and 27 years old and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…To draw the link between the dangerous effect of ‘high self-esteem’ as a trait of the hyperthymic temperament and PSU, studies have shown that a high level of self-esteem protects the person from developing PSU. However, subjects suffering from PSU tend to seek instant answers to preserve their self-esteem [ 95 ]. It could be noted that in order not to lose their high but fragile self-esteem, subjects with hyperthymic temperament develop PSU.…”
Section: Discussionmentioning
confidence: 99%
“…To draw the link between the dangerous effect of ‘high self-esteem’ as a trait of the hyperthymic temperament and PSU, studies have shown that a high level of self-esteem protects the person from developing PSU. However, subjects suffering from PSU tend to seek instant answers to preserve their self-esteem [ 95 ]. It could be noted that in order not to lose their high but fragile self-esteem, subjects with hyperthymic temperament develop PSU.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some researches have shown no correlation between smartphone addiction and creative achievement (Upshaw et al, 2022) or divergent and convergent thinking (Linares & Sellier, 2021; Olson et al, 2023; Rodríguez et al, 2020), other studies have demonstrated that the use of smartphones correlates positively with mind-wandering (Marty-Dugas et al, 2018; Müller et al, 2021), which is considered a correlate of creativity (Agnoli et al, 2018). These findings suggest that the relationship between mobile phone use and creative ideation remains to be fully elucidated.…”
Section: Mobile Phone Use and Creative Ideationmentioning
confidence: 99%
“…Penggunaan smartphone dalam pembelajaran matematika dapat mempengaruhi kualitas belajar siswa, terutama jika aplikasi atau materi yang digunakan tidak sesuai dengan kurikulum atau tidak dapat meningkatkan kompetensi siswa (Papadakis et al, 2021); 4) Isolasi: Penggunaan smartphone yang berlebihan dapat menyebabkan siswa menjadi kurang interaktif dalam kelas dan kurang berkoordinasi dengan siswa lain (Fook et al, 2021); 5) Kesehatan: Penggunaan smartphone yang berlebihan dapat menyebabkan masalah kesehatan seperti sakit kepala, kurang tidur, dan gangguan posisi tubuh (Demir & Sümer, 2019); dan 6) Kemampuan berpikir: Penggunaan smartphone yang berlebihan dapat mempengaruhi kemampuan berpikir kritis dan analitis siswa dalam menyelesaikan masalah matematika (Rodríguez et al, 2020).…”
Section: Diskusiunclassified